2020
DOI: 10.1002/pon.5310
|View full text |Cite
|
Sign up to set email alerts
|

Digital interventions to facilitate patient‐provider communication in cancer care: A systematic review

Abstract: Objective: Patient-provider communication is a critical component of cancer care. Digital tools have been applied to facilitate cancer care and patient-provider communication. However, to date, there is no systematic review on this growing body of literature. The objective of this study is to identify the existing digital interventions to improve patient-provider communication among cancer patients and survivors, summarize their characteristics, and synthesize the outcomes of these interventions. Methods: We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 59 publications
1
55
0
Order By: Relevance
“…[2][3][4] Fortunately, recent reviews of studies conducted in the pre-COVID-19 era have found that digital interventions appear to facilitate patientprovider communication in cancer care. 7 At least throughout the remainder of 2020, until an effective and immunogenic vaccine is developed and widespread population vaccination is achieved, these approaches will need to be maintained for supportive cancer care.…”
Section: Key Pointsmentioning
confidence: 99%
“…[2][3][4] Fortunately, recent reviews of studies conducted in the pre-COVID-19 era have found that digital interventions appear to facilitate patientprovider communication in cancer care. 7 At least throughout the remainder of 2020, until an effective and immunogenic vaccine is developed and widespread population vaccination is achieved, these approaches will need to be maintained for supportive cancer care.…”
Section: Key Pointsmentioning
confidence: 99%
“…[23,24] Digital interventions may not only target palliative care problems; rather, they may provide additional support related to health access, information, or mental health resources. [25,26] The adoption of such digital support systems can improve the overall patient experience and satisfaction regarding palliative care. Moreover, such platforms may enable healthcare providers to make real-time decisions for their patients and address occupational concerns and stresses that they may experience.…”
Section: The Rise Of Digital Health: Psychosocial Interventions In Pamentioning
confidence: 99%
“…Overall, digital tools can be integrated into institutional or health systems interventions where multiple individuals, including patients, caregivers, and healthcare providers, can interact, emphasizing on how those systems can inform the unmet needs among the individuals and facilitate effective caregiving for everyone. [25] The level and contents of those services can be customized for different groups based on their unique psychosocial needs. For example, mental health components can be incorporated for patients and caregivers who may experience psychological distress or other mental health problems.…”
Section: The Rise Of Digital Health: Psychosocial Interventions In Pamentioning
confidence: 99%
See 1 more Smart Citation
“…A growing number of clinical trials have shown good outcomes for digital mental health interventions (Angrish et al, 2020;Cavazos-Rehg et al, 2020;Hong, Hossain, & Chou, 2020;Price et al, 2014). However, there are a few examples of implementations that can be seen as failures.…”
mentioning
confidence: 99%